The Effects of Freezing on the Processing Characteristics and Palatability Attributes of Fresh Pork Legs - B. G. Sapp; Dwain D. Johnson; Larry E. Eubanks; Joel H. Brendemuhl (EDIS)
AN202, a 5-page report by B. G. Sapp, D. D. Johnson, L. E. Eubanks, and J. H. Brendemuhl, presents the results of a study to ascertain if de-boning and vacuum packaging of fresh hams for frozen storage had any effect on the processing qualities and oxidative rancidity of the cured ham as compared to the traditional method of freezing and storing of fresh bone-in hams. Includes references. Published by the UF Department of Animal Science, May 2008.